Diagnostic value of computed tomography myocardial perfusion to detect coexisting microvascular dysfunction in patients with obstructive epicardial coronary disease. (3rd October 2022) - Hada, M; Hoshino, M; Sugiyama, T; Misawa, T; Nagamine, T; Ueno, H; Matsuda, K; Sayama, K; Yonetsu, T; Sasano, T; Kakuta, T
Abstract: Background: The usefulness of computed tomography myocardial perfusion (CTP) to assess hemodynamically significant epicardial coronary artery lesions has been previously reported. However, the diagnostic value of quantitative evaluation of absolute coronary flow by CTP to detect microvascular dysfunction remains unknown. Purpose: The aim of study is to assess the diagnostic value of CTP to evaluate coronary microvascular dysfunction (CMD) in patients with significant epicardial coronary stenosis, and to analyze the predicting factors for lesions with CMD. Methods: Sixty-eight chronic coronary syndrome patients with de novo single functionally significant stenosis (Fractional flow reserve [FFR] <0.80) were investigated. CMD was defined by the index of microcirculatory resistance (IMR) ≥25. Clinical characteristics and CTP findings were compared between the two groups with and without CMD (CMD, n=29, non-CMD, n=39, respectively). The computed tomography angiography (CCTA) assessment included CTP findings and quantitative and qualitative assessment of plaques. Results: In wire-based analysis, FFR, coronary flow reserve (CFRwire) and IMR were 0.68 (0.59–0.74), 1.71 (1.24–2.88), and 22.6 (15.1–34.5), respectively. In CTP analysis, culprit territory regional absolute myocardial blood flow (MBF) at rest (rest-MBF) and hyperemia (hyperemic-MBF) were evaluated semi-automatically. CTP-derived CFR (CFRCTP) was calculated as hyperemic-MBF divided by rest-MBF. Rest and hyperemic-MBF and CFRCTP were 0.83 (0.64–1.03) ml/min/g, 2.14 (1.30–2.92) ml/min/g, and 2.19 (1.44–3.37). In the lesions with CMD, hyperemic-MBF was significantly lower than those without CMD (1.68 [0.84–2.44] vs 2.31 [1.67–3.34] ml/min/g, p=0.015) and the prevalence of CFRCTP<2.0 was higher in the lesions with CMD than those without CMD (62.1% vs 28.2%, p=0.007). CCTA analysis showed that fibrofatty and necrotic core component (FFNC) volume was greater in the lesions with CMD than in the lesions without CMD (31.8 [19.0–48.9] vs 25.1 [17.2–32.1] mm 3, p=0.045). The multivariable logistic regression analysis, hyperemic-MBF and FFNC volume were independent predictors for lesions with CMD (Odds ratio [OR] 0.583 [0.355–0.958], p=0.033 and OR 1.040 [1.010–1.070], p=0.018). Conclusion: Quantitative assessment of absolute coronary flow by CTP and comprehensive plaque analysis by CCTA may help detect coexisting subtended microvascular dysfunction in patients with functionally significant epicardial coronary lesions. Further studies are needed to elucidate the clinical significance of coexisting CMD in CCS patients. Funding Acknowledgement: Type of funding sources: None.